(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nafisah W, Prabaningtyas S, Witjoro A, Saptawati RT, Rodiansyah A. 2022. Exploration non-symbiotic nitrogen-fixing bacteria from several lakes in East Java, Indonesia. Biodiversitas 23: 1752-1758. Potential microorganisms, mainly nitrogen-fixing bacteria spread in almost lake areas in East Java. The biogeochemical processes that occur between biotic-biotic or biotic-abiotic factors can accelerate the growth of autotrophic microorganisms in waters as like microalgae. Non-symbiotic nitrogen-fixing bacteria in the water can supply nitrogen to support the growth of microalgae. This study is aimed to explore and calculate the ammonium concentration produced by non-symbiotic nitrogen-fixing bacteria that isolated from several lakes in East Java. The highest ammonium producing bacteria were characterized based on morphology, physiology, and genetic with 16S rRNA gene sequencing. The bacterial isolates were screened with a nitrogen-free bromothymol blue medium to select bacterial isolates capable of fixing nitrogen. The content of NH3/NH4 was produced by isolates of nitrogen-fixing bacteria was measured by using the prodac test kit NH3/NH4. The ammonium concentration was calculated with Nessler’s reagent by using the spectrophotometry method at a wavelength of 425 nm. The result was obtained 31 isolates of non-symbiotic nitrogen-fixing bacteria. The bacterial isolate B2 exhibited highest activity of fixing nitrogen that produced ammonium (14.46 mg/L) among the other screened bacteria. The morphological and physiological characterization from that isolate was identified as genus Bacillus, whereas the genetic characterization similar to Bacillus paramycoides, that included in the Bacillus cereus group.